Capacity utilization and business investment - Streever, Donald Courtney (Urbana : University of Illinois, 1960)
The purpose of this study is to present an analysis of the relationship of business capital expenditures to variations in the rate of utilization of productive capacity. The study presents a brief review of the theoretical background of the hypothesis and its significance to business cycle and growth theory; interview and other studies of the determinants of investment and; the relationship of investment and the utilization of capacity for four major industrial classifications- manufacturing and mining, electric power utilities, communications, and railroads.
Issued also as thesis, University of Illinois.
Includes bibliographical references: p. 73-76.
ne 05/08/2021
Loans
Keywords: Capital investments